TKA wear testing input after kinematic and dynamic meta-analysis: Technique and proof of concept - Franta, L.; Kronek, J.; Suchánek, J. (Wear, 2011)
Simulation under conditions that respect real kinematics and dynamics of applying a load to the components can be an important instrument to predict the behaviour of new prosthesis designs and materials during the time of wear. Various studies have shown that the gait of TKA patients is different from the gait of healthy subjects. Therefore the time behaviour which is proposed in the ISO standard does not really represent the loads in TKA patients. Most of the current testing laboratories simulate continuous walking according to ISO 14°243, but neglect everyday activities. It is impossible to simulate the real movement of specific patients. Hence, a loading mode (with respect to daily activities) was determined, based on experimental studies. The length and frequency of individual loading were also defined. The testing mode includes normal walk, sitting–standing, cycling, stair climbing and walking with extra load. The device is able to perform the ISO walk as well. The simulator has been designed to reproduce the configuration of the implanted prosthesis. The simulated motion is described by periodic harmonic function, which enables setting the proper position in required time. The duration of a compound load process reflecting daily activities lasted 240 min. The compound load consists of elementary sub cycles, each of them representing one motion phase. A relaxation phase is inserted between all active movements. Several differences were observed between known experimental results and the present standard ISO 14°243.